Studies on Spectral Properties of Co(II), Ni(II) and Cu(II) Complexes with Ninhydrine and Ninhydrine Oximes - Rai, H.C.; Rai, B.K.; Thakur, R.K. (Asian Journal of Chemistry, 2010)
A series of complexes of the type ML1-3CI2, ML1-3CI2Y2, where M = Co(II), Ni(II) and Cu(II), L1= ninhydrine, L2 = ninhydrine monoxime, L3 = ninhydrine dioxime, Y = NH3 or pyridine, have been synthesised and characterised by elemental analysis, molar conductivity, electronic absorption spectra and infrared spectra. On the basis of experimental data the complexes of the type ML1-3Cl2 are found to be square planar whereas complexes of the type ML1-3Cl2 Y2 are found to be octahedral. The complexes are found to be non-electrolytic in nature on the basis of molar conductivity value.